Nuclease treatment enhanced the ameliorative effect of yeast culture on epidermal mucus, hepatic lipid metabolism, inflammation response and gut microbiota in high-fat diet-fed zebrafish. Issue 131 (December 2022) - Zhao, Yajie; Hao, Qiang; Zhang, Qingshuang; Yang, Yalin; Ran, Chao; Xu, Qiyou; Wu, Chenglong; Liu, Wenshu; Li, Siming; Zhang, Zhen; Zhou, Zhigang
Abstract: As a functional feed additive, yeast cultures are rich in nucleotides, and adding extra nuclease can significantly increase the content of nucleotides in yeast culture. In this experiment, the effects on growth, epidermal mucus, liver and intestinal health of zebrafish were evaluated by supplementing the yeast culture or nuclease-treated yeast culture with a high-fat diet (HFD). One-month-old zebrafish were fed four diets: normal diet (NORM), HFD, yeast culture diet (YC), and nuclease-treated yeast culture diet (YC (N)) for three weeks. Results showed that the complement 4 activity of the epidermal mucus in YC (N) group was significantly higher than those in HFD and YC groups (P < 0.05). The YC and YC (N) significantly reduced the content of hepatic triglyceride caused by HFD (P < 0.05). Moreover, compared with the YC group, the YC (N) significantly increased the expression of lipolysis genes, such as PPARα, PGC1α, ACOX3 (P < 0.05). Compared with the YC group, the YC (N) group significantly increased the expression of liver pro-inflammatory factors TNFα, IL-6, IL-1β and anti-inflammatory factors TGFβ, IL-10 (P < 0.05). The diet YC and YC (N) significantly improved the height of the intestinal villus (P < 0.05). Compared with the HFD group, the YC (N) group significantly increased the expression of intestinal pro-inflammatory factors TNFα, IL-6 and anti-inflammatory factors TGFβ, IL-10 (P < 0.05). The YC (N) group significantly decreased the abundance of intestinal Proteobacteria and Acinetobacter, and increased the abundance of intestinal Actinobacteria, Mycobacterium and Rhodobacter (P < 0.05). In conclusion, compared with the supplement of yeast culture, nuclease treated yeast culture can further alleviate the adverse effects of HFD on liver and intestinal health, and be used as feed additives for the nutritional and immune regulation of fish. Highlights: Nuclease treated yeast culture improved the immunity of epidermal mucus of zebrafish fed high-fat diet. Nuclease treated yeast culture reduced triglyceride accumulation and improved liver injury of zebrafish fed high-fat diet. Nuclease treated yeast culture improved the intestinal morphology and inflammatory response of zebrafish fed high-fat diet. Nuclease treated yeast culturer regulated the intestinal microbiota structure of zebrafish fed high-fat diet.